Variables associated with college teachers participation in decision making in Western Visayas - Penachos, Manuel Raca 1940-
The subjects were 744 college teachers from 12 private tertiary institutions. Personal variables (age, sex, teaching experience, educational attainment, appointment status, academic rank, number of training seminars attended, experience in clubs/organizations, attitude towards participation) and organizational variables (leadership style, effect of school policy, effect of faculty population, type of school) were associated with the extent of participation in academic and administrative decision making. The strongest predictors are number of seminars attended and total number of training hours in seminar workshops for private college teachers and leadership style for the public sector. College teachers as a whole and by type of school had "moderate" extent of participation in academic and administrative decision making.